Virtual Education: A Brief Overview of Its Role in the Current Educational System - José Miguel Orellana Parapi; Lilis Imas Maesaroh; Basuki Basuki; Edi Sunjayanto Masykuri (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2020)
Virtual education is a growing and evolving system that creates new opportunities for forming and upgrading people’s skills with a non-presential factor, which allows students from different regions and backgrounds to gain instant access to quality education and knowledge. In recent years, many online platforms have been joining to these new systems allowing to create a virtual environment, even professional institutions, such as colleges and universities, are offering their entire specialty in different online programs. Although, online education has evolved and improved since its apparition after the internet commercialization, many problems still remain unsolved and challenging its effectiveness; self-motivations and virtual drop-out are one of the common factor among virtual learners, besides the lack of required technology and resources in different places, especially in developing countries. Even there are problems, virtual education is changing the way how we consume educational content and it is helping to connect students and teachers all over the world in again-to-gain way, so in the coming years, its role is expected to be more critical in our education system.